ASPECTS OF REAL ESTATE PRIVATIZATION OF THE AUTONOMOUS REPUBLIC OF ADJARA (BASED ON THE EXAMPLE OF GODERDZI SKI RESORT) (Globalization and Business, 2023)
In the Autonomous Republic of Adjara, the establishment of ski resort on Goderdzi Pass is important for the development of recreation resources and as well as for the central government, which dedicates a significant amount of financial resources from both local and the central budget. Consequently, it is important to consider the ongoing processes of resort privatization. This interest is further intensified by the direct sale of a large amount of real estate. This article analyses the assessment aspects of real estate transfer in the form of direct sales and discusses the factors hindering the development of the resort, as well as the expected consequences of massive real estate privatization. So far, the mechanisms of privatization of property owned by the Autonomous Republic of Adjara and the legislation in force within this area, including strengths and weaknesses are discussed. Based on the law, the goal of privatization in the form of direct sale is to transfer the property right to the customer, who fully and conscientiously fulfils the condition(s) set for property privatization in the form of direct sale. The following can be assessed by the projects and activities carried out by the bidder in the past. The examples of direct selling discussed in the article clearly show that there are frequent cases when the transfer of property in the form of direct sale takes place to entrepreneurial entities registered a few days earlier, which excludes from consideration their experience in this particular field. Apart from that, in the legislative part of maintaining the profile as well as in the part of the employment of the locals, different deadlines and terms of condition are set for various companies which differ greatly without any regularity. Due to the abovementioned reasons, the investors who initially agree with the contract initiate amendments which causes changes to be made to the initial agreement. Often, these changes contradict the general plan for the development of the Goderdzi Ski Resort and have an overall negative impact on the stance of the Autonomous Republic of Adjara due to frequent extension of the deadline for the investment execution. Based on the results of the research, it is recommended to create a document (computing formula) that will allow the property management body to determine the minimum amount of employees and the amount of investment during the development of the investment package, as well as the minimum period of profile maintenance.